Effect of carnosine supplementation on lipid profile, fasting blood glucose, HbA1C and insulin resistance: A systematic review and meta-analysis of long-term randomized controlled trials. (January 2020) - Peng, Weixia; Mao, Peijun; Liu, Lijun; Chen, Keli; Zhong, Yaqin; Xia, Wenping; Guo, Qiaohong; Tan, Shing Cheng; Rahmani, Jamal; Kord Varkaneh, Hamed; He, Peixiang
Highlights: Carnosine supplementation improves HbA1C levels. Carnosine supplementation do not have effect on fasting glucose. Carnosine supplementation do not have effect on lipid profile. Abstract: Objective: Glucose disorders and dyslipidemia are closely associated with obesity and metabolic disease. The purpose of this study was to investigate the effect of Carnosine supplementation on lipid profile, fasting blood glucose, HbA1C and Insulin resistance. Method: MEDLINE/PubMed, Scopus and Web of sciences were investigated to identify relevant articles up to June 2019. The search strategy combined the Medical Subject Heading and Title and/or abstract keywords. The combined effect sizes were calculated as weight mean difference (WMD) using the random-effects model. Between study heterogeneity was evaluated by the Cochran's Q test and I 2 . Results: Four RCTs studies investigated Carnosine use versus any control for at least 2 weeks were identified and analyzed. Overall results from the random-effects model on included studies, with 184 participants, indicated that carnosine intervention reduced HbA1C levels in intervention vs control groups (WMD: −0.92 %, 95 % CI: −1.20, −0.63, I 2 :69 %). Four studies, including a total of 183 participants, reported TG changes as an outcome measure variable, but combined results did not show significant reduction in this outcome (WMD: −14.46 mg/dl, 95 % CI: −29.11, 0.19, I 2 :94 %). Furthermore, combined results did not show any significant change in HOMA-IR, Cholesterol, fasting blood sugar, or HDL-C. Conclusion: Carnosine supplementation results in a decrease in HbA1C, but elicits no effect on HOMA-IR, Cholesterol, fasting blood sugar, TG and HDL-C. Future studies with a larger sample sizes, varied doses of carnosine, and population-specific sub-groups are warranted to confirm, and enhance, the veracity of our findings.